2011
DOI: 10.1016/j.bcp.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-based drug screening in primary ovarian carcinoma cultures identifies intracellular iron depletion as a promising strategy for cancer treatment

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. The results indicate the feasibility of using PCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…Among 4 431 a priori defined gene sets, the gene set “Chuang oxidative stress response up” exhibited the highest enrichment score for VLX60 (Figure 5A). Furthermore, in accordance with earlier published results [5], the GSEA showed that genes associated with HIF1 signaling were induced by exposure to VLX50, as opposed to VLX60 (Figure 5C–5D). This hypoxia response associated with VLX50 treatment has been shown to be consistent with iron chelation as mechanism of action [5].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Among 4 431 a priori defined gene sets, the gene set “Chuang oxidative stress response up” exhibited the highest enrichment score for VLX60 (Figure 5A). Furthermore, in accordance with earlier published results [5], the GSEA showed that genes associated with HIF1 signaling were induced by exposure to VLX50, as opposed to VLX60 (Figure 5C–5D). This hypoxia response associated with VLX50 treatment has been shown to be consistent with iron chelation as mechanism of action [5].…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, in accordance with earlier published results [5], the GSEA showed that genes associated with HIF1 signaling were induced by exposure to VLX50, as opposed to VLX60 (Figure 5C–5D). This hypoxia response associated with VLX50 treatment has been shown to be consistent with iron chelation as mechanism of action [5]. Hallmark genes associated with apoptosis were enriched in cells exposed to either drug (Figure 5F–5G).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…VLX600 was more potent than other iron chelators (i.e. Triapine (3-aminopyridine-2-carboxaldehyde-thiosemicarbazone)8, CPX, VLX5019, and deferoxamine) (Fig. 3A–G).…”
Section: Resultsmentioning
confidence: 97%
“…To measure confluence, phase contrast images were collected over time, taking updates every 2 to 3 h, and confluence was measured, as described previously. 8,9 Data Analysis Data were exported from the IncuCyte software into Microsoft Excel. All data were then imported into GraphPad Prism software (La Jolla, CA) for graphing and statistical analysis.…”
Section: Measuring Cell Confluencementioning
confidence: 99%